Pengaruh Ukuran Perusahaan, Profitabilitas, Leverage, dan Kualitas Audit terhadap Agresivitas Pajak: (Studi Empiris pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar pada Bursa Efek Indonesia Periode 2020 – 2023) - Rurry Septiani; Suryani Suryani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of the research is to find the influence of variables Firm Size, Profitability, Leverage, and Audit Quality on Tax Aggressivity. The sample in study includes 35 companies sub-sector food and beverage listed in Indonesia Stock Exchange (BEI) in the period 2020-2023. The sampling technique used purposive sampling method and obtained 140 sample data from 35 companies. The analytical tool used is multiple linear regression analysis using the Statistical Product and Service Solution (SPSS) Version 22 program. The result of this study indicate that profitability has a significant positive effect